Evaluation of a Clinical Decision Support System for Dyslipidemia Treatment (HTE-DLPR) by QoE questionnaire - Alberto Zamora; Carme Carrion; Marta Aymerich; Xavier Castells; Lidia Blanco; Anabel Martin-Urda; Guillen Paluzie; Dolors Capellá; Roberto Elosua (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
Introduction: Clinical decision support systems (CDSS) are computer systems designed to assist clinicians with patient-related decision making, such as diagnosis and treatment. CDSS have shown to improve both patient outcomes and cost of care.Methods: A multi-center observational prospective study was conducted. Ten physicians agreed to participate. Seventy-seven patients with high or very high cardiovascular risk were included. After using CDSS for dyslipidemia (HTE-DLPR) for a 3 months period, participants were asked to evaluate their experience with HTE-DLPR using a quality of experience questionnaire (QoE) tool for mHealth applications.Results: Total score on the QoE was 3.89 out of 5. The highest scores were received for precision, ease of use and content quality. The lowest scores were given to security, appearance and performance. Physicians were in strong agreement with the 1st HTEDLPR recommendation in 86.1% and the system’s use was described as comfortablein 85% of cases. Users positively evaluated the development of a new version of HTEDLPR in the future receiving a total score of 4.25 out of 5.Conclusions: A CDSS for dyslipidemia (HTE-DLP) has been positively evaluated by physicians using QoE questionnaire.